2015
DOI: 10.1371/journal.pone.0136129
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Biodiversity on the Rocks: Macrofauna Inhabiting Authigenic Carbonate at Costa Rica Methane Seeps

Abstract: Fig 2, "Temperature and dissolved oxygen profile generated near Jaco Wall, Costa Rica from a CTD cast," is incorrect and is a duplication of Fig.1, "Carbonates formations in different habitats on the Costa Rica Margin." The authors have provided a corrected version here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The RV Atlantis surveyed the Pacific continental margin of Costa Rica from October 24th to November 5th, 2018, from the continental slope to the offshore seamounts across a subduction zone. In this region, several methane-rich seeps have been detected (Sahling et al, 2008;Levin et al, 2012Levin et al, , 2015. All sediment cores were collected by the human-occupied vehicle (HOV) Alvin equipped with mechanical, maneuverable arms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RV Atlantis surveyed the Pacific continental margin of Costa Rica from October 24th to November 5th, 2018, from the continental slope to the offshore seamounts across a subduction zone. In this region, several methane-rich seeps have been detected (Sahling et al, 2008;Levin et al, 2012Levin et al, , 2015. All sediment cores were collected by the human-occupied vehicle (HOV) Alvin equipped with mechanical, maneuverable arms.…”
Section: Methodsmentioning
confidence: 99%
“…The Costa Rican ETP comprises a chain of mountains and submarine volcanoes across the subduction zone of the Cocos and Caribbean tectonic plates. Here, there is a high diversity of microhabitats ( Lizano, 2001 ; Protti et al, 2012 ; Rojas and Alvarado, 2012 ) including methane seeps ( Sahling et al, 2008 ; Levin et al, 2012 , 2015 ). Previous studies have shown high endemism and diversity of macro- and microorganisms in this region ( Rusch et al, 2007 ; Cortés, 2008 , 2019 ; Rojas-Jiménez, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RV Atlantis surveyed the Pacific continental margin of Costa Rica from October 24 th to November 5 th , 2018, from the continental slope to the offshore seamounts across a subduction zone. In this region, several methane-rich seeps have been detected (Sahling et al, 2008; Levin et al, 2012, 2015). All sediment cores were collected by the human-occupied vehicle (HOV) Alvin equipped with mechanical, maneuverable arms.…”
Section: Methodsmentioning
confidence: 99%
“…The first studies on the biology of this area reported dominance of tubeworms (Siboglinidae), clam aggregations (Vesicomyidae), mussel beds (Bathymodiolinae), and bacterial mats (Sahling et al, 2008). Levin et al (2015) found that Mound 12 has some of the highest density (~200 to more than 600 individuals per 200 cm 2 , the average size of a rock) and diversity (~26 species per rock) of deep-sea fauna on rocks from tubeworm bushes and mussel beds under active seepage among several sites in the Costa Rican Pacific margin. The faunal ensemble composition at Mound 12 shows interannual variability due to natural changes in seepage activity (Pereira et al, 2021).…”
Section: Samplingmentioning
confidence: 99%